Model Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Karakter Religius Siswa di SMA Negeri 1 Rancabungur - Hidayah, Farhah; Qowaid; Arman Paramansya (Jurnal Dirosah Islamiyah, 2024)
Religious character is one of the characters that needs to be developed in every student to instill good behavior in accordance with the path that has been guided in the Al-Quran and Hadith. This research is limited by focusing this research on Islamic Religious Education learning models and the curriculum implemented by schools in improving students' religious character. This research uses a qualitative approach. The subjects of this research were school principals, school principals, PAI teaching staff and staff. The data collection was carried out by sourced from several PAI learning documents available at the school, as well as interviews with parties related to PAI learning, and researcher observations with field observations of the process of implementing PAI learning at SMA Negeri 1 Rancabungur. The results of the research show that improving the quality of learning begins with planning before learning, there is reciting of al-Quran, the learning process emphasizes student activity. PAI learning cannot be separated from the lecture method, PAI learning model with various variations using the inquiry learning model, in an effort to provide quality student learning with expository, cooperative learning. In addition to providing varied learning methods, teachers also provide guidance, habituation, advice, motivation and uswatun hasanah or role models. Implementation: First, the process of providing religious understanding to students. Second, holding religious activities. Third continuous supervision. Supporting and inhibiting factors include the following: Supporting Factors, First, parents, Second, school facilities and resources, Third, Example. The inhibiting factors include: Internal factors include students who do not have a strong will to carry out activities of a religious character. Meanwhile, external factors, from teachers and parents, and finally environmental factors.